1053. Biofilm Production and Clinical Characteristics of S. maltophilia Causing Persistent or Relapsing Bacteremia. (26th November 2018) - Kang, Seung Ji; Oh, Tae Hoon; Jung, Younggon; Kim, Seong Eun; Kim, Uh Jin; Jang, Hee-Chang; Park, Kyung-Hwa; Jung, Sook-In
Abstract: Background: This study aimed to identify clinical or microbiological factors related to persistence or recurrence of Stenotrophomonas maltophilia bacteremia in adult patients. Methods: S. maltophilia isolated from blood in two tertiary hospitals between 2011 and 2017 were investigated. Persistent bacteremia was defined as the consecutive blood culture positive for ≥5 days after initiation of appropriate antibiotics therapy. Relapse was defined as isolation of S. maltophilia from blood after completion of antibiotics treatment for the first episode of bacteremia. Biofilm formation was assessed in 96-well polystyrene plate with Trypticase Soy Broth using 0.5% crystal violet staining. The presence of smf -1 gene was detected by polymerase chain reaction. Results: Of total 100 patients with S. maltophilia bacteremia, 10 of persistent, 8 of relapsing, and 46 of nonpersistent, nonrelapsing cases were investigated. The presence of indwelling urinary catheter ( P = 0.011), nasogastric tube ( P = 0.003), mechanical ventilator treatment ( P = 0.001), and previous colonization of S. maltophilia ( P = 0.016) were more frequently observed in patients with persistent bacteremia compared with nonpersistent, nonrelapsing bacteremia cases. In patients with relapsing bacteremia, hematologic malignancy ( P = 0.022), neutropenia ( P = 0.001), and concomitant isolation of S. maltophilia in clinical samples other than blood ( P = 0.041) were more common than nonpersistent, nonrelapsing bacteremia patients. Catheter-related infection (37.0%) followed by pneumonia (28.3%) was the most common primary focus of nonpersistent, nonrelapsing bacteremia whereas pneumonia was the most frequent cause of bacteremia in both of persistent and relapsing cases (40.0% and 50.0%). Most of isolates (63 of 64) were susceptible to cotrimoxazole. The resistance to levofloxacin were comparable among isolates from persistent, relapsing and nonpersistent, nonrelapsing cases (10.0% vs. 12.5% vs. 15.2%, P = 0.988). Biofilm formation ability was not significantly different between three groups (optical density at 595, mean ± SD, 0.69 ± 0.34 vs. 0.78 ± 0.33 vs. 0.70 ± 0.33, P = 0.529). The smf-1 gene was found in all isolates. Conclusion: More careful treatment approaches to patients with risk factors for S.maltophilia treatment failure should be warranted. Disclosures: All authors: No reported disclosures.